Normal Pressure Hydrocephalus: Vascular White Matter Changes on MR Images Must Not Exclude Patients from Shunt Surgery - Tullberg, Mats; Jensen, Christer; Ekholm, Sven; Wikkelsø, Carsten (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: White matter changes such as periventricular hyperintensity (PVH) and deep white matter hyperintensity (DWMH) are associated with both periventricular edema and ischemic white matter degeneration. Their diagnostic and predictive value in normal pressure hydrocephalus (NPH) is unclear. To identify prognostically important changes, we classified PVH and DWMH at MR imaging in a large series of patients with NPH, before and after ventriculoperitoneal shunt surgery.METHODS: Axial proton density– and T2-weighted turbo spin-echo sequences and coronal T1-weighted sequences were performed on a 0.5-T imager in 34 patients with NPH, before and 3 months after shunt surgery. PVH at the anterior, central, and posterior thirds of the lateral ventricles was assessed on transaxial images with a semiquantitative five-step scale describing the extension (in mm) and shape of the PVH. DWMH was quantified with a four-step scale. The number of cortical and subcortical lacunar infarctions, the flow void sign, and the width of the third and lateral ventricles were registered. Gait ability, need for sleep, urinary incontinence, living conditions, and psychometric test performance were assessed pre- and postoperatively.RESULTS: After shunt surgery, 25 patients improved and nine did not. PVH, DWMH, and other MR imaging variables before shunting did not differ between groups, and no MR imaging variable could predict the clinical effect of shunt surgery. Postoperatively, the width of PVH was reduced in the improved patients, and clinical improvement correlated with reduction in PVH. Only the irregular type of PVH located at the frontal horns was reduced postoperatively. The presence of risk factors or MR imaging changes normally associated with cerebrovascular disease had no negative influence on the outcome of shunt surgery.CONCLUSION: The presence of DWMH or subcortical lacunar infarctions in NPH did not predict a poor outcome from shunt surgery and should not be used as exclusion criteria for shunting. No MR imaging findings could predict outcome of shunt surgery in patients with NPH. Clinical improvement after surgery is associated with reduction in the irregular type of PVH located around the frontal horns.